Indeterminate results of interferon gamma release assays in the screening of latent tuberculosis infection: a systematic review and meta-analysis - Zhou, Guozhong; Luo, Qingyi; Luo, Shiqi; Chen, Hongbo; Cai, Shunli; Guo, Xin; He, Jian; Xia, Yuan; Li, Hanse; Zhou, Yingchen; Zhang, Yazhou; Song, Chao (Frontiers in Immunology, 2023)
Objectives We aimed to evaluate the indeterminate rate of interferon gamma release assays (IGRAs) in the detection of latent tuberculosis infection (LTBI). Methods On 15 November 2022, we searched the PubMed® (National Library of Medicine, Bethesda, MD, USA), Embase® (Elsevier, Amsterdam, the Netherlands), and Cochrane Library databases in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Two investigators independently extracted the study data and assessed their quality using a modified quality assessment of diagnostic accuracy studies (i.e., QUADAS-2) tool. A random-effects model was used to calculate pooled results. Results We included 403 studies involving 486,886 individuals and found that the pooled indeterminate rate was 3.9% (95% CI 3.5%–4.2%). The pooled indeterminate rate for QuantiFERON®-TB (QFT) was similar to that for T-SPOT®.TB (T-SPOT) [odds ratio (OR) = 0.88, 95% CI 0.59–1.32]; however, the indeterminate rate for a new generation of QFT (QFT-plus) was lower than that of T-SPOT (OR = 0.24, 95% CI 0.16–0.35). The indeterminate rate in the immunocompromised population was significantly higher than that in healthy controls (OR = 3.51, 95% CI 2.11–5.82), and it increased with the reduction of CD4+ cell count in HIV-positive patients. Children’s pooled indeterminate rates (OR = 2.56, 95% CI 1.79–3.57) were significantly higher than those of adults, and the rates increased as the children’s age decreased. Conclusion On average, 1 in 26 tests yields indeterminate IGRA results in LTBI screening. The use of advanced versions of the QuantiFERON-TB assay (QFT-plus), may potentially reduce the occurrence of an indeterminate result. Our study emphasizes the high risk of immunosuppression and young age in relation to indeterminate IGRA, which should receive more attention in the management of LTBI. Systematic review registration PROSPERO https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42020211363, CRD42020211363.